Efektivitas pajak daerah dan retribusi daerah terhadap pendapatan asli daerah Kabupaten Bondowoso - Adellia Anugerah; Kuni Handayawati; Annisa Fatimah (University of Merdeka Malang, 2023)
This study aimed to determine the effectiveness of the regional taxes and regional levies on The Regional Original Income (PAD) at the Regional Revenue Agency of Bondowoso Regency in 2017-2021 (before and during the Covid-19 pandemic) and their policies. This research was processed by a qualitative descriptive method with interviews and documentation as data collection methods. The research data sources came from the Government Agency Performance Report (LKIP) of Bapenda and the Bondowoso Regency Regional Budget Realization Report for 2017-2021. The effectiveness ratio used as an analytical tool was in the form of a formula which was a comparison between the taxes and the budget multiplied by one hundred percent which was adjusted to the criteria for measuring effectiveness. The results showed the effectiveness of the regional taxes and the levies before the Covid-19 pandemic (2017-2019) with very effective criteria, namely 100% on the regional taxes and 106% on the regional levies. Meanwhile, the effectiveness of regional taxes and levies during the Covid-19 pandemic (2020-2021) has an effective criterion of 95% on the regional taxes and 75% on the regional levies.